A Multitargeted Approach: Organorhodium Anticancer Agent Based on Vorinostat as a Potent Histone Deacetylase Inhibitor. (17th June 2020) - Hanif, Muhammad; Arshad, Jahanzaib; Astin, Jonathan W.; Rana, Zohaib; Zafar, Ayesha; Movassaghi, Sanam; Leung, Euphemia; Patel, Kamal; Söhnel, Tilo; Reynisson, Jóhannes; Sarojini, Vijayalekshmi; Rosengren, Rhonda J.; et al.
Abstract: The combination of more than one bioactive moiety in a multitargeted anticancer agent may result in synergistic activity of its components. Using this concept, bioorganometallic compounds were designed to feature a metal center, a 2‐pyridinecarbothioamide (PCA), and a hydroxamic acid, which is found in the anticancer drug vorinostat (SAHA). The organometallics showed inhibitory activity in the nanomolar range against histone deacetylases (HDACs) as the key target for SAHA. In particular, the Rh complex was a potent inhibitor of HDAC6 over HDAC1 and HDAC8. Whereas this complex was highly cytotoxic in human cancer cells, it showed low toxicity in hemolysis studies and zebrafish, demonstrating the role of the metal center. For this complex a slightly reduced expression of vascular endothelial growth factor receptor 2 (VEGFR2) was established, which was upregulated by SAHA. This finding indicates that the new organometallics display different modes of action than their bioactive components. Abstract : Creating synergies : The combination of more than one bioactive moiety resulted in an organometallic compound featuring a metal center, a 2‐pyridinecarbothioamide (PCA), and a hydroxamic acid, which is found in the anticancer drug vorinostat (SAHA). The compound displayed different modes of action than its components, supporting the development of non‐conventional anticancer drugs.